Occupational safety in China: Safety climate and its influence on safety-related behavior - Zhu, C.; Fan, David; Fu, G.; Clissold, G. (Sage Publications Ltd., 2010)
The improvement of health and safety standards within the organizational context is an important issue of global concern. China’s occupational health and safety (OHS) has increasingly drawn national and international attention as it has not kept pace with its globalization of production and trade. The traditional approach to managing workplace safety in China has focused on the technical aspects of engineering systems and processes, and it has attributed the majority of workplace accidents and injuries to unsafe working conditions instead of the unsafe work practices of employees. However, there has been a fundamental shift in the safety management research carried out in many countries and across diverse industries, which aims to measure the impact of attitudinal, organizational, cultural, and social dimensions on occupational safety. This article examines the relationship between safety climate and safety-related behavior in the Chinese context and draws implications for the management of occupational safety in China.